Optimalisasi Manajemen Operasional Dalam Meningkatkan Kinerja Asuransi Syariah di Era Digital - Nurhayati Harahap; Putri Nawarni Harahap; Rizki Khoiril Waladi Siahaan; Arya Advany (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
This study aims to analyze the optimization of operational management through digital transformation in Islamic insurance companies. The research employed a library research method with a qualitative descriptive approach. The results indicate that business process digitalization, human resource development, digital risk governance, and customer experience enhancement improve operational efficiency, productivity, service quality, and corporate competitiveness. The use of technologies such as Artificial Intelligence (AI), Big Data Analytics, and Cloud Computing also supports faster business processes and better decision-making. Therefore, digital transformation supported by competent human resources and compliance with sharia principles is essential for improving the performance and sustainability of Islamic insurance companies.